The relationship between corporate social responsibility and financial performance of Iraqi Corporations: A literature review - Azam Abdel Hakeem Khalid Ahmed (Tanjong Malim, 2019)
The relationship between corporate social responsibility and financial performance of Iraqi Corporations: A literature review by Azam Abdel Hakeem Khalid Ahmed